Ictus isquémico como forma de presentación de una disección aórtica tipo A. - Cátia Ribeiro Santos; Cláudia Antunes; Cátia Faria; João Crespo Santos (Sociedade Galega de Medicina Interna, 2021)
Acute aortic dissection is a rare but lethal cardiac disease involving the aorta and it remains a challenge to diagnose and treat. The range of clinical features is extremely variable. Neurologic symptoms are also present in rare cases but often lead to a misdiagnosis because they mimic stroke. We report a case of a 71-year-old male with aortic dissection presented with acute onset altered mental status and left arm weakness. Aortic dissection presented with neurological symptoms is rare and requires high level of suspicion, especially in cases with unusual presentation.